PENGARUH METODE MEMBACA BERULANG TERHADAP KELANCARAN MEMBACA SISWA KELAS III DI SD NEGERI 12 PEGUYANGAN DENPASAR - Desak Made Wiwik Krisdayanti; Ni Gusti Ayu Made Yeni Lestari; Ni Nyoman Suastini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Reading fluency is one of the fundamental skills that elementary school students must master to support their learning achievement. However, the reading fluency of Grade III students at SD Negeri 12 Peguyangan Denpasar was still relatively low. This study aimed to determine the effect of the Repeated Reading method on the reading fluency of Grade III students at SD Negeri 12 Peguyangan Denpasar. This study employed a quantitative approach using a Pre-Experimental Design with a One-Group Pretest–Posttest Design. The research subjects consisted of 34 students selected using the saturated sampling technique. Data were collected through reading tests, observations, interviews, and documentation. The data were analyzed using descriptive and inferential statistics with the assistance of IBM SPSS Statistics Version 22, including the Shapiro–Wilk normality test and the Paired Sample t-test. The results showed that the mean pretest score was 60.24, while the mean posttest score increased to 81.35. The results of the Paired Sample t-test showed a significance value of 0.000 < 0.05, indicating that H₀ was rejected and H₁ was accepted. Therefore, it can be concluded that the Repeated Reading method has a significant effect on the reading fluency of Grade III students at SD Negeri 12 Peguyangan Denpasar.